Linking Jasmonic Acid to Grapevine Resistance against the Biotrophic Oomycete Plasmopara viticola - Guerreiro, Ana; Figueiredo, Joana; Sousa Silva, Marta; Figueiredo, Andreia (Frontiers in Plant Science, 2016)
Plant resistance to biotrophic pathogens is classically believed to be mediated through salicylic acid (SA) signaling leading to hypersensitive response followed by the establishment of Systemic Acquired Resistance. Jasmonic acid (JA) signaling has extensively been associated to the defense against necrotrophic pathogens and insects inducing the accumulation of secondary metabolites and PR proteins. Moreover, it is believed that plants infected with biotrophic fungi suppress JA-mediated responses. However, recent evidences have shown that certain biotrophic fungal species also trigger the activation of JA-mediated responses, suggesting a new role for JA in the defense against fungal biotrophs. Plasmopara viticola is a biotrophic oomycete responsible for the grapevine downy mildew, one of the most important diseases in viticulture. In this perspective we show recent evidences of JA participation in grapevine resistance against P. viticola, outlining the hypothesis of JA involvement in the establishment of an incompatible interaction with this biotroph. We also show that in the first hours after P. viticola inoculation the levels of OPDA, JA, JA-Ile and SA increase together with an increase of expression of genes associated to JA and SA signaling pathways. Our data suggests that, on the first hours after P. viticola inoculation, JA signaling pathway is activated and the outcomes of JA-SA interactions may be tailored in the defense response against this biotrophic pathogen.